2010
DOI: 10.1002/mrm.22673
|View full text |Cite
|
Sign up to set email alerts
|

Mapping proteoglycan‐bound water in cartilage: Improved specificity of matrix assessment using multiexponential transverse relaxation analysis

Abstract: Association of MR parameters with cartilage matrix components remains an area of ongoing investigation. Multiexponential analysis of non-localized transverse relaxation data has previously been used to quantify water compartments associated with matrix macromolecules in cartilage. We extend this to mapping the proteoglycan-bound water fraction (wPG) in cartilage, using mature and young bovine nasal cartilage model systems, towards the goal of matrix component-specific imaging. wPG from mature and young bovine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 36 publications
(48 reference statements)
7
71
0
Order By: Relevance
“…Assignments of NIR (80,84) and FTIR (19,39,50) proteoglycans than the native cartilage (20) and focal degenerative lesions in human osteoarthritic AC contained less proteoglycans than the surrounding healthy tissue (24). The univariate methods are easy to implement, and, therefore, they have been applied in many studies (25)(26)(27)(28)(29)(30)(31)(32). Collagen and proteoglycan concentration and collagen integrity maps produced using the univariate parameters in human tibial AC are shown in Figure 2.…”
Section: ¡1mentioning
confidence: 99%
“…Assignments of NIR (80,84) and FTIR (19,39,50) proteoglycans than the native cartilage (20) and focal degenerative lesions in human osteoarthritic AC contained less proteoglycans than the surrounding healthy tissue (24). The univariate methods are easy to implement, and, therefore, they have been applied in many studies (25)(26)(27)(28)(29)(30)(31)(32). Collagen and proteoglycan concentration and collagen integrity maps produced using the univariate parameters in human tibial AC are shown in Figure 2.…”
Section: ¡1mentioning
confidence: 99%
“…Because of the low fraction and difficulty in measuring the water tightly bound to the collagen component, which has an extremely short T2 (24), most multicomponent T2 mapping techniques involve the use of bicomponent models that allow assessment of only the fast-relaxing water tightly bound to proteoglycan and slow-relaxing bulk water loosely bound to the hydrophilic glycosaminoglycan side chains of proteoglycan components of cartilage (25)(26)(27)(28). Authors of previous studies have shown that the fraction of the fast-relaxing water tightly bound to the proteoglycan component is a sensitive and specific measure of the proteoglycan content of cartilage (24)(25)(26). However, authors of previous multicomponent T2 mapping studies (24)(25)(26)(27)(28) have been limited by their use of CarrPurcell-Meiboom-Gill techniques with long acquisition times, which allowed for cartilage assessment on only a single section of ex vivo specimens.…”
Section: Study Groupmentioning
confidence: 99%
“…Authors of previous studies have shown that the fraction of the fast-relaxing water tightly bound to the proteoglycan component is a sensitive and specific measure of the proteoglycan content of cartilage (24)(25)(26). However, authors of previous multicomponent T2 mapping studies (24)(25)(26)(27)(28) have been limited by their use of CarrPurcell-Meiboom-Gill techniques with long acquisition times, which allowed for cartilage assessment on only a single section of ex vivo specimens. Multicomponent driven equilibrium single-shot observation of T1 and T2 (mcDESPOT) is a rapid method for multicomponent T2 mapping (29)(30)(31)(32)(33)(34).…”
Section: Study Groupmentioning
confidence: 99%
“…It is likely that during engineered tissue growth, both the T 1 and T 2 relaxation times would decrease due to accumulation of both proteoglycans and collagen. It is possible to separate the contributions of water, proteoglycans and collagen content to the observed T 2 data of engineered cartilage using multiexponential analysis, 38,39,94 but such experiments require a very high SNR, hence, use of signals from the entire sample, not from individual image pixels. Nevertheless, using this technique, Reiter et al have found that the proteoglycan component in cartilage tissue taken from young and mature bovine nasal cartilage was highly correlated with T 2 and with the biochemical analysis.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Nevertheless, using this technique, Reiter et al have found that the proteoglycan component in cartilage tissue taken from young and mature bovine nasal cartilage was highly correlated with T 2 and with the biochemical analysis. 94 Using sodium and T 1rho MRI, Novotny et al 41 have shown that culture of highdensity porcine chondrocytes produced a similar amount of proteoglycans in 8 weeks as found in natural cartilage. In addition, Li et al 33 have shown a statistically significant correlation between MT parameters (bound water fraction and cross-relaxation rates) and the GAG content-engineered cartilage tissue for the period of 3 weeks.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%